2010
DOI: 10.1590/s0100-40422010000400044
|View full text |Cite
|
Sign up to set email alerts
|

Gestão das inovações incrementais, o caso Omeprazola

Abstract: Recebido em 15/12/08; aceito em 14/10/09; publicado na web em 25/3/10 MANAGEMENT OF INCREMENTAL INNOVATIONS, THE CASE OMEPRAZOLE. Our report shows the strategies adopted by pharmaceutical industry in the development of incremental innovations, through the development carried out after the launch of omeprazole. Some improvements are really necessary and others are used only as a market strategy and evergreening.Keywords: incremetal innovation; omeprazole; patent. INTRODUÇÃOA essência do sistema patentário é est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The Brazilian government should consider growth and development of the pharmaceutical area in its strategic plans. Brazil has national pharmaceutical companies, which invest in incremental innovation as an important source of economic and technological development (Bastos, 2005;Shadlen, 2011;Lourenço et al, 2010). The fact that there have been no applications from Brazilian pharmaceutical companies for clopidogrel polymorphs makes it clear that they should consider incremental innovations in the pharmaceutical area as a viable strategy for pharmaceutical industry growth and further reinforces the importance of this topic.…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian government should consider growth and development of the pharmaceutical area in its strategic plans. Brazil has national pharmaceutical companies, which invest in incremental innovation as an important source of economic and technological development (Bastos, 2005;Shadlen, 2011;Lourenço et al, 2010). The fact that there have been no applications from Brazilian pharmaceutical companies for clopidogrel polymorphs makes it clear that they should consider incremental innovations in the pharmaceutical area as a viable strategy for pharmaceutical industry growth and further reinforces the importance of this topic.…”
Section: Discussionmentioning
confidence: 99%
“…A 2010 analysis of the Food and Drug Administration (FDA) website found that, in the US, omeprazole was protected by a total of 40 patents [22], constituting a 'patent thicket'. Another example of such a thicket is highlighted in an article on the Australian market [23] which asserts that, in addition to the original patent for omeprazole, there were 61 additional patents, two of which clearly appear to have prevented generics from entering the market.…”
Section: Regulatory Aspectsmentioning
confidence: 99%